Prácticas de exposición solar en padres de niños en Atención Primaria, Santiago, Chile - Castrillón V., M. Adriana; Matamala C., José Manuel; Feldman F., Marcos; Gajardo G., Constanza; Valenzuela, Carlos Y.; Zemelman D., Viviana (Revista Hospital Clínico Universidad de Chile, 2013)
The incidence of skin cancer has increased many times during the past several decades in the white population. The purpose of this study was to analyse the awareness of parents and caregivers towards sun exposure and to study their sun protection behaviour towards their children. The survey was conducted in a primary health care setting in the north of Santiago, Chile, from June to July, 2008. A suitable questionnaire of 23 multi choice questions comprising items examining awareness, knowledge and sun protection towards their children was used. Parents whose child was between the ages of 6 months to 11 years old were included in the study. 437 parents and care givers were interviewed. Children´s ages were between 6 months to 11 years old with a median age 3.6 (SD 3.2). Statistical analysis was performed by the Chi square test. In relation to parental knowledge, 99.5% of parents and care givers were aware of the link “sun-skin cancer”. A 31.4% of the parents declared that their children were exposed to the sun in the summer between 2 and 4 hours between 11 AM and 4PM hrs. A 13.9 % of children had been sun burned once in their life. Regarding sun protection behaviour in the summer day at the hottest hours, 85.4% of parents protected their children with sunscreen, 82.6% made them wear a hat, 70.2% make them to seek the shade. 32.3% of the parents reported the use of sunglasses on their children, 23.6% reported to make them wear protective clothes. Regarding the use of sunscreen on their children in the summer, 43.2% declared to use it regularly. Also, a very small percentage of children used sunscreen in the swimming pool and on the beach. In summary, the children in this study were showed to be reasonably sun protected; however, further public health interventions may increase the knowledge of parents and improve even further their sun protection behaviour towards their children.